Power output during competitive cycling time trial performances - Davison, R. C.; Coleman, D. A.; Balmer, J.; Bird, S. R. (1999)
Until recently it has only been possible to indirectly estimate power output during cycling time trial performances using mathematical models. However since the development of the SRM Powercranks it is now possible to directly measure and record power outputs during any race, but to date there is no published data on the typical power outputs that can be maintained across the different time trial distances. The aim of this study was therefore to collate field recordings of power output with laboratory test data to establish the relative exercise intensity maintainable across a range of time trial distances. Power output recordings were collected using SRM Powercranks, over a three year period from 8 experienced male club cyclists (age, 30±7 years; mass, 74.4±4.7 kg), in time trial races ranging from 16.1km to 12 hours. In addition all riders underwent a maximal aerobic power test to determine peak power output (PPO) within 4 weeks of each race. The mean PPO from all maximal tests was 433.9±20.4 W, the percentage of the PPO values that were maintained for the duration of each race are illustrated in the graph below. No single line adequately described the relationship between %PPO and the duration of the race, therefore the data was fitted with a linear relationship (y =-0.0302x + 72.282, R2=0.92) for distances > 80.5 km and a power function (y =96.668x-0.0689, R2=0.8) for distances < 80.5 km. This data suggests a dependence on the aerobic system for races of >~100 min and an increasing contribution from the anaerobic system for the shorter races. From this data it was estimated that the anaerobic contribution added ~12 and 28 W to the average power for 40.2 and 16.1 km races respectively. This information could be used to establish appropriate exercise intensities for the range of time trial distances.